Adsorptive Voltammetry for the Determination of Ochratoxin A Using Enrichment Effect by Cationic Surfactants. Issue 10 (2nd July 2018) - Sultana, Ayesha; Sazawa, Kazuto; Okazaki, Takuya; Islam, Md. Saiful; Hata, Noriko; Sugawara, Kazuharu; Kuramitz, Hideki
Abstract: A rapid and simple electrochemical method was utilized for the determination of the presence of classic fungal metabolite ochratoxin A (OTA) based on differential pulse adsorptive voltammetry, using the carbon nanotube paste (CNTP) electrode. OTA showed a clear oxidation peak, and the CNTP electrode exhibited a more sensitive response to OTA oxidation than the glassy carbon, the plastic formed carbon, and the carbon paste electrodes. The addition of long‐chain cationic surfactants, such as benzethonium chloride, cetyltrimethylammonium bromide, and benzyldimethyltetradecylammonium chloride (zephiramine), enhanced the electrochemical response of OTA. Under optimized experimental conditions, the calibration plots are linear in the 5×10 −6 −5×10 −5 M OTA concentration range, and the limit of detection is 1.1×10 −6 M. In order to improve the selectivity for OTA determination, we attempted to combine this adsorptive stripping voltammetric technique with "sequestration electrochemistry, " based on the specific interaction occurring between bovine serum albumin (BSA) and OTA. The peak current of OTA oxidation decreased substantially as a result of OTA‐BSA binding. Furthermore, it was demonstrated that the application of this proposed method of hydrodynamic adsorptive voltammetry, using a micro‐droplet and a rotating disk electrode, improves the approach's sensitivity and reduces the time and sample volume required for the analysis. Abstract :